Analisis Supervision For Succesfull Schools - Eka Saputra, Darwin; Eka Salindri, Agesta; Adhelmi; Sahniarti; Handayani; Harto, Kasinyo; Astuti, Mardiah (The Future of Education Journal, 2024)
This study aims to analyze the role of supervision in improving teacher performance, student academic achievement, and raising awareness of the importance of effective supervision in every aspect of school management. The research method used is a literature study, analyzing references from articles, journals, and other sources from the internet. The results indicate that effective supervision plays a crucial role in creating successful schools. Therefore, school management should invest time and resources in the training and development of supervisors, enabling them to provide the necessary support to teachers, principals, and education supervisors to achieve optimal educational goals. More broadly, the study shows that supervision is not merely an administrative task but an integral part of teacher professional development and the overall improvement of educational quality. Properly trained supervisors can directly impact teacher performance, which in turn contributes to student academic achievement. Thus, it is essential for all stakeholders—including government, school administrators, and communities—to understand that effective supervision is key to creating a conducive and high-quality learning environment. Educational success depends not only on curriculum or facilities but also on a well-functioning and sustainable supervision system.